The Influence of Principal Policy, Teacher Performance and School Facilities on the Quality of Education at SMPN 1 Mapia Bomomani - Magdalena Boga; Dety Mulyanti; Theresia Widyanti (Journal on Education, 2024)
The quality of education at SMPN 1 Mapia Bomomani still appears to be not optimal, or it could be said that it is still far from what was expected. The not yet optimal quality of education at SMPN 1 Mapia Bomomani is a phenomenon that does not stand alone, because it is correlated with many influencing factors. Regarding this phenomenon, the assumption arises that the principal's policy, teacher performance and school facilities are three factors that have a positive influence on the quality of education at SMPN 1 Mapia Bomomani. This research aims to analyze the influence of principal policies, teacher performance and school facilities on the quality of education at SMPN 1 Bomomani. This research uses the following techniques: The research sample is 22 respondents taken from a population of 22 teachers; data analysis using quantitative analysis and qualitative analysis; and using Multiple Regression statistics. From the discussion of the research results, the following conclusions are obtained: 1) The influence of principal policies, teacher performance, and school facilities on the quality of education at SMPN 1 Mapia Bomomani is still low due to the weak performance of teachers in planning teaching programs, implementing learning activities and evaluating learning outcomes. 2) The influence of the principal's policy on the quality of education at SMPN 1 Mapia Bomomani has a direct effect on improving education. 3) The influence of teacher performance on the quality of education at SMPN 1 Mapia Bomomani does not improve the quality of education. 4) The influence of school facilities on the quality of education at SMPN 1 Mapia Momomani has a direct effect on improving the quality of education. Based on these conclusions, the suggestions that need to be made are that teachers must be able to adapt to school culture as a system of values and habits that produce optimal performance so that the quality of education can improve, school principals must implement appropriate leadership management with full exemplary, build commitment, and always motivate the improvement of teacher performance in carrying out their duties so that the quality of education can improve. The Dogiyai District Education Office always runs coaching programs for school principals and teachers and motivates teachers to improve their performance so that the quality of education can improve.